Saint Lucia. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Santa Lucia during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as greenhouse, seedlings, harvesting, training, agrotourism, trade, protected agriculture, waste management, pesticides. , production, organic agriculture and technology. Likewise, technical support was provided for the management of water resources, post-harvest handling, leadership, biodiversity, storage of agrochemicals, safety, emergency aid against disasters caused by Hurricane Tomás and the control of diseases and pests, such as black sigatoka. Finally, work was done on the inclusion of women and young people and on the value chains of vegetables, fruits, cassava, flowers, pineapple, cocoa, dairy, pork, and trees.